Mobility and tourist locations. The case of Martinique Island, a French territory in the Caribbean - Olivier Dehoorne; Huhua Cao (Belgeo)
This paper contributes to the analysis of the mobility system through strategic sites represented by tourist locations, mirrors of globalisation. Tourist locations exist merely through human flows: varied and complex flows between migrations and tourism. In the context of North-South border control, emerging tourist locations situated at the margins of the richest regions sometimes represent an opportunity to bypass the regional borders. Through the analysis of mobility in the Caribbean area, the previous categories used to describe the types of mobility demonstrate their limits when faced with the complexity of flows and growing interactions. Subsequently, a microanalysis of Martinique Island enables us to reflect upon the social aspects of this mobility and to ponder on the issues concerning the old and new political and socio-spatial borders.